2017
DOI: 10.18632/oncotarget.16709
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0005986 inhibits carcinogenesis by acting as a miR-129-5p sponge and is used as a novel biomarker for hepatocellular carcinoma

Abstract: Circular RNAs (circRNAs), a class of long-time-ignored noncoding RNA, have been revealed as multifunctional RNAs in recent years. However, the diagnostic values and the mechanism of most circRNAs in hepatocellular carcinoma (HCC) remain unknown. In this study, we revealed that the expression level of hsa_circ_0005986 in HCC was significantly lower than that in adjacent non-tumorous tissues (P < 0.001). Its levels in HCC cell lines, HepG2, SMMC7721, Huh7, MHCC97L, MHCC97H, and HCCLM3 were significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 50 publications
3
83
0
Order By: Relevance
“…To date, several circRNAs have emerged as new biomarkers in cancers. For example, hsa_circ_0000190 could serve as a biomarker for gastric cancer diagnosis, hsa_circ_0005986 was used as a biomarker in the diagnosis of HCC, and circular RNA ciRS‐7 was identified as a prognostic biomarker in colorectal cancer . In this study, we investigated that hsa_circ_0000567 was downregulated in CRC tissues and CRC cell lines (Figure ).…”
Section: Discussionmentioning
confidence: 84%
“…To date, several circRNAs have emerged as new biomarkers in cancers. For example, hsa_circ_0000190 could serve as a biomarker for gastric cancer diagnosis, hsa_circ_0005986 was used as a biomarker in the diagnosis of HCC, and circular RNA ciRS‐7 was identified as a prognostic biomarker in colorectal cancer . In this study, we investigated that hsa_circ_0000567 was downregulated in CRC tissues and CRC cell lines (Figure ).…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, Fu et al . found both hsa_circ_0005986 and hsa_circ_0004018 were downregulated in HCC tissues and cells . Han et al .…”
Section: Discussionmentioning
confidence: 98%
“…indicated that the upregulation of circ‐ITCH inhibited the in vitro growth and in vivo tumorigenesis of esophageal squamous cell carcinoma cells . Knockdown of hsa_circ_0005986 accelerated the proliferation and the cell cycle of HCC cells . Circ‐MTO1 suppressed HCC tumor growth by targeting miR‐9 and upregulating P21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations